Sensory regulation of meal sorting in Aedes aegypti mosquitoes - Emi Maekawa; Anupama A. Dahanukar (Scientific Reports)
Abstract Meal sorting in mosquitoes is a phenomenon whereby ingested blood and sugar meals are directed to different destinations in the alimentary canal. We undertake a systematic analysis and show that entry of blood in the midgut is influenced by blood components, temperature, and feeding mode, while sugar solutions are directed to the crop in a dose-dependent manner. Sweet and nutritive sugars, like sucrose and maltose, enter the crop more efficiently compared to non-sweet or non-nutritive sugars. Additionally, the robustness of meal sorting declines with mosquito age and is compromised in mutants of candidate thermoreceptors. Proper blood meal sorting is crucial for optimal egg production, as disruption of this process by adding sucrose results in reduced fecundity. Furthermore, certain amino acids essential for vitellogenesis are preferentially directed to the midgut. Our findings provide new insights into the meal sorting mechanism, with implications for mosquito reproduction and vectorial capacity.